Effect of Leader Member Exchange on Innovative Work Behaviour throught Work Eengagement as a Mediation - Ratnasari, Dita; Wulansari, Nury Ariani (Management Analysis Journal, 2019)
The purpose of this study to examine the influence of leader member exchange (LMX) on innovative work behavior is mediated by work engagement. The population in this study were employees of the plywood manufacturing division and the manufacture of plywood waste crafts PT. Karya Jaya Kendal as many as 200 people. The sample used was 133 people using proportional random sampling sampling technique. The method of collecting data using a questionnaire measured by a Likert scale. Data analysis method uses hypothesis testing and path analysis test using SPSS for Windows version 21 analysis. The results of this study are leader member exchange has a positive and significant effect on innovative work behavior. Work engagement mediates member exchange leaders on innovative work behavior. Work engagement mediates on innovative work behavior.